Music Cognition and Affect in the Design of Technology-Enhanced Music Lessons - Macrides, Elena; Angeli, Charoula (Frontiers in Education, 2020)
The present study addresses the lack of an instructional design methodology that guides the integration of technology in music listening and composition activities, and enriches the framework of Technological Pedagogical Content Knowledge (TPCK)—an essentially cognitive model– with the affective domain. The authors herein provide many examples that illustrate the music design principles and the expanded Technology Mapping instructional design process that have been proposed in previously published work. The practical examples provide concrete ideas on how to transform the musical materials into more understandable forms and how to associate them with emotions using technology. Besides its practical contribution, the research has also a theoretical significance for the theory of TPCK as it examines the interrelations between music content, technology, cognition, and affect, and identifies discipline-specific aspects of TPCK that include the affective domain. The empirical evidence of 191 secondary school students presented within the context of a music composition task using the software MuseScore, supports that both the TPCK framework as well as the proposed music guidelines can effectively guide teachers in designing lessons with technology while incorporating effect. Through the 4E perspective, technology and the proposed approach are viewed as agents of a distributed system that can support the embodied minds to develop musical and emotional understanding.